Developing productive projects in rural and indigenous areas of the state of Oaxaca: Student experiences - Damián Simón, Javier (Acta Universitaria, 2022)
Meeting the demands of a society is one of the purposes of university training. The objective of this work is to describe the limitations in the development of proposals for productive projects in rural areas, presented by students of the ninth semester of a major in business at the Papaloapan University, a rare analysis in the study area. Limitations were found in identifying ideas for productive projects in rural contexts due to the students’ academic training, wich is different to rural and indigenous sector, coupled with little interest on the part of municipal authorities and heads of public agencies related to productive projects; such low interest is reflected on the lack of punctuality in the times, failure to comply with agreements, and strong criticism of the proposals presented. It is concluded that the university, before involving students in this type of activities, must train teachers in this subject and establish links between the various public agents to allow students from their business profile to make contributions to their home communities.